2015 IEEE International Conference on Software Maintenance and Evolution (ICSME) 2015
DOI: 10.1109/icsm.2015.7332487
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for maintenance of PLC-software and its related hardware for automated production systems: Selected industrial Case Studies

Abstract: The specific challenges for maintenance of software and its related hardware for the domain of automated Production Systems is discussed. Presenting four industrial case studies from renowned and world market leading German machine and plant manufacturing companies, these challenges and different solution approaches are introduced with a focus on software architectures to support modularity as a basis for maintaining long-living automated Production Systems. Additionally, most critical aspects hindering classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Vogel-Heuser et al [16] confirmed the five architectural levels proposed by ISA 88 [17] by analyzing the SW architecture of companies from the MM and PM industry. Further, [18] confirms that the reuse potential of application-specific POUs correlates with the architectural hierarchy levels they are located on: the higher the level of a POU, the lower is its potential for reuse.…”
Section: Rq4 What Are the Causes And Consequences Of Control Sw Compmentioning
confidence: 87%
See 1 more Smart Citation
“…Vogel-Heuser et al [16] confirmed the five architectural levels proposed by ISA 88 [17] by analyzing the SW architecture of companies from the MM and PM industry. Further, [18] confirms that the reuse potential of application-specific POUs correlates with the architectural hierarchy levels they are located on: the higher the level of a POU, the lower is its potential for reuse.…”
Section: Rq4 What Are the Causes And Consequences Of Control Sw Compmentioning
confidence: 87%
“…Further, the authors in [4] divide the lifecycle of aPS into two main phases: At first, engineering, which includes testing/quality assurance, and second, after acceptance test, operation and maintenance. Due to the nature of aPS, changes resulting from new products, unforeseen raw material, or environmental conditions often have to be made on-site [4], [16].…”
Section: Characteristics Of Aps Suppliersmentioning
confidence: 99%
“…The approach's feasibility is shown by analyzing (1) a typical function block from an industrial context and (2) an application scenario which combines this block with a second one. According to Vogel-Heuser et al [6], software faults are mainly caused on these levels of system design: the atomic and the basic level.…”
Section: Application Examplementioning
confidence: 99%
“…Vogel-Heuser et al has shown in [6] that faults mostly occur on lower software architecture levels. Subsequently, errors must often be handled on the atomic or basic module layer.…”
Section: Introductionmentioning
confidence: 99%
“…The architectural levels can be used recursively, i.e., each level can consist of all module types of the more fine-grained levels." [8].…”
Section: Introductionmentioning
confidence: 99%